Legal Aid For The Poor - Gatot Efrianto; Nia Tresnawaty (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The definition of a state is a territory with a sovereign government, governed by law, and having a permanent population. Every resident living within a state is obligated to obey the laws established in that state. This is especially true in Indonesia as a state based on the rule of law, as asserted in the 1945 Constitution (UUD 1945) Article 1 paragraph (3): “The State of Indonesia is a state based on law.” However, even though Indonesia is a state of law, in reality, law enforcement in the country remains very weak. This is exacerbated by numerous public perceptions and negative assumptions resulting from failed legal implementation, such as the widespread belief that “the law is sharp downward but blunt upward.” In society and state life, the law should be the commander in every aspect of life, aiming to create justice, maintain order, and protect individual rights. But what does justice truly mean in Indonesia? Is justice as simple as 1+1 = 2 or 2+2 = 4? If justice is defined that way, then the lower class should feel the same fairness as the upper class, particularly when it comes to legal matters. The term “lower class” here refers to marginalized groups who face various forms of injustice, including limited access to the judiciary, poverty, legal illiteracy, and many others. In light of this, this paper will discuss the problems and the concept of legal aid as a right and obligation that must be guaranteed for the poor. The fact remains that currently, poor communities still struggle to access legal aid due to their difficult economic conditions, which often remain unaccommodated.